2009
DOI: 10.1111/j.1365-263x.2009.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Remembering and repeating childhood dental treatment experiences: parents, their children, and barriers to dental care

Abstract: Acknowledging the influence of parental dental experience would help ensure that parents of young children access routine care for their children and themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
1
18
1
8
Order By: Relevance
“…It has been observed that negative experiences of dental care during childhood may manifest during adulthood, through parents delaying dental treatment for themselves and their children [20]. In our study, a striking absence of any memories relating to childhood dental visits was observed amongst Oral Health Non-prioritisers.…”
Section: Discussioncontrasting
confidence: 50%
“…It has been observed that negative experiences of dental care during childhood may manifest during adulthood, through parents delaying dental treatment for themselves and their children [20]. In our study, a striking absence of any memories relating to childhood dental visits was observed amongst Oral Health Non-prioritisers.…”
Section: Discussioncontrasting
confidence: 50%
“…It was found that parents who visited the dentist themselves for the sake of prevention were five times more likely to take their children to dental exams than parents who did not go for regular dental checkups [20]. Smith and Freeman [22] found that parents' experience with dental care during childhood influenced their behavior and decision-making regarding their children's dental health, while research by Esa et al [23] asserted that fear of dental treatment often contributes to inadequate development of dental health among children and adults. Despite technological developments in modern dental medicine, fear of dental treatment and pain is still widespread.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Therefore, it may be proposed that a social gradient may exist for dental anxiety due to dental caries and the effect of frightening dental treatment experiences in childhood. Moreover, as dental anxiety is an independent predictor of opportunistic and declining dental visiting patterns in adulthood, it may be proposed that dental fears persist across the life course …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as dental anxiety is an independent predictor of opportunistic and declining dental visiting patterns in adulthood, 9 it may be proposed that dental fears persist across the life course. 10,11 Theorizing in this way suggests that a social gradient may exist with those from lower socioeconomic groups experiencing more dental anxiety and hence more dental caries. Therefore, it is of little surprise that earlier research reports of associations between dental anxiety and various perceived and clinical oral health measures after controlling for socio-demographic factors.…”
mentioning
confidence: 99%